Validation of Oxford Cognitive Screen: Executive Function(OCS-EF), a tablet-based executive function assessmenttool amongst adolescent females in rural South Africa - Rowe, Kirsten; Duta, Mihaela (Wiley Online, 2021)
Short, reliable, easily administered executive function (EF) assessment tools are needed to measure EF in low- andmiddle-income countries, particularly in sub-Saharan Africa given the prevalence of human immunodeficiency virus(HIV)-associated neurocognitive disorder. We administered Oxford Cognitive Screen — Executive Function (OCS-EF)to 932 rural South African females (mean age 19.7 years).
Keywords: Cognition; Executive function; Low- and middle-income countries; Africa; Adolescents